Supracerebellar Infratentorial Infratrochlear Trans-Quadrangular Lobule Approach to Pontine Cavernous Malformations. Issue 3 (12th January 2021) - Rutledge, Caleb; Raper, Daniel M S; Rodriguez Rubio, Roberto; Winkler, Ethan A; Abla, Adib A
Abstract: BACKGROUND: Brainstem cavernous malformations with symptomatic hemorrhage have a poor natural history. Those without a pial or ependymal presentation are often observed given the morbidity of resection. Surgical removal is considered only in patients with accessible lesions that have repeated symptomatic hemorrhagic. OBJECTIVE: To describe a novel supracerebellar infratentorial infratrochlear trans-quadrangular lobule approach to safely resect lesions in the upper pons. METHODS: We use a hybrid paramedian/lateral suboccipital craniotomy in the gravity-dependent supine position. Opening the cerebellomesencephalic fissure over the tentorial surface of the cerebellum brings the trochlear nerve, branches of the superior cerebellar artery, and the quadrangular lobule of the cerebellum into view. Removal of small a portion of the quadrangular lobule defines an entry point on the superomedial aspect of the middle cerebellar peduncle, and a surgical trajectory aimed superior to inferior. RESULTS: A total of 6 patients underwent this approach. All presented with symptomatic hemorrhage and all cavernous malformations were completely resected. Five patients were improved or unchanged with modified Rankin scale scores of 1 or 2. CONCLUSION: The trans-quadrangular lobule approach allows safe resection of upper pontine cavernous malformations along a superior to inferior trajectory.